2014
DOI: 10.14445/22315381/ijett-v16p242
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glass Powder on the Properties Of Concrete

Abstract: Abstract-Glass is commonly used in building / construction industries and large amount of glass is powdered daily. The disposal of waste glass is an environmental issue as waste glass causes disposal problem. Today the construction industry is in need of finding cost effective materials for increasing the strength of concrete structures. Glass powder finer than 600 µ is reported to have pozzolanic behaviour. An attempt is made to investigate the possibility of using the waste glass powder as the partial replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…The strength obtained at constant rates and at 84 days of testing of M2 (10%), M3 (15%) and M4 (20%) mixture achieved 88% compressive strength of the control concrete. Bhat and Rao (2014) concluded that the compressive strength of concrete containing 20% of glass powder presents a maximum strength compared to control concrete; this result is consistent with Sakale et al (2016). Figure 3 shows the different compressive strength results as a function of glass powder content in the concrete.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The strength obtained at constant rates and at 84 days of testing of M2 (10%), M3 (15%) and M4 (20%) mixture achieved 88% compressive strength of the control concrete. Bhat and Rao (2014) concluded that the compressive strength of concrete containing 20% of glass powder presents a maximum strength compared to control concrete; this result is consistent with Sakale et al (2016). Figure 3 shows the different compressive strength results as a function of glass powder content in the concrete.…”
Section: Introductionsupporting
confidence: 88%
“…This is due to the low-density value of glass used (2.58) compared to cement (3.15). The same result was confirmed by Bhat and Rao (2014). Keerio et al (2017) observed that the density of hardened concrete increases with the substitution of 5%, 10% and 15% of cement by glass waste; the maximum increase of 1.25% in the control concrete was observed when replacing 10% of cement by glass powder.…”
Section: Introductionsupporting
confidence: 60%
“…That is why density is one of the most critical factors that must be considered during concrete mix designs. Concrete density with glass is shown in Figure 5 as per past studies [ 49 , 60 , 61 , 67 ]. A study reported that concrete density is 1.25% more than the reference concrete at 10% substitution of waste glass by the weight of binders [ 68 ].…”
Section: Fresh Propertiesmentioning
confidence: 84%
“…ANOVA is very useful when examining the multi-item scales mutual in market research. The author functioned in the research of [15] illustrated that the glass is an unknown substantial containing a high percentage of silica content (SiO2) i.e.72% with waste glass once ashore to a highly fine powder (600 microns) responds to alkali in cement & cementations production in assisting the donate to a strong expansion. [16], replacing the coconut shell with coarse aggregate once studying the transportation characteristics of concrete with coconut shells (CS) with replacing of coarse aggregate.…”
Section: Literature Reviewmentioning
confidence: 99%